2021
DOI: 10.3390/ijerph18052577
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Spatial-Temporal Evolution Characteristics and Spatial Network Structure of Tourism Eco-Efficiency in the Yangtze River Delta Urban Agglomeration

Abstract: Based on the panel data of 41 cities in the Yangtze River Delta from 2008 to 2017, this paper constructs an evaluation indicators system for urban tourism eco-efficiency. By measuring the tourism eco-efficiency in the Yangtze River Delta urban agglomeration, we analyze its spatial-temporal evolution characteristics. Furthermore, the modified gravity model and social network analysis are introduced to explore the spatial network structure of tourism eco-efficiency and its evolution trend.The results show that:(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…At the same time, this paper takes knowledge innovation as the input factor of tourism industry development efficiency evaluation, pays attention to tourism application technology, management mode and talent training, and emphasizes the modernization role of tourism development platform and tools, which is the improvement of the input-output index system of tourism development efficiency. After constructing a reasonable evaluation index system, EBM model was selected in this paper, including radial and non-radial distance functions, which made up for the deficiencies of traditional DEA model and non-radial SBM model to some extent [ 74 ]. The traditional radial DEA model requires that all inputs and outputs change in the same proportion and ignores the influence of non-radial relaxation variables.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this paper takes knowledge innovation as the input factor of tourism industry development efficiency evaluation, pays attention to tourism application technology, management mode and talent training, and emphasizes the modernization role of tourism development platform and tools, which is the improvement of the input-output index system of tourism development efficiency. After constructing a reasonable evaluation index system, EBM model was selected in this paper, including radial and non-radial distance functions, which made up for the deficiencies of traditional DEA model and non-radial SBM model to some extent [ 74 ]. The traditional radial DEA model requires that all inputs and outputs change in the same proportion and ignores the influence of non-radial relaxation variables.…”
Section: Discussionmentioning
confidence: 99%
“…At present, scholars' research on ecological efficiency mainly focuses on two aspects, the first is about the measurement of ecological efficiency. Some scholars studied the ecological efficiency of regional tourism based on the perspective of China's regional tourism, it is found that the tourism industry and ecology efficiency exist obvious spatial spillover, although it is often considered to be environmentally friendly tourism industry, but in recent years, the rapid growth of tourism has failed to compensate for the destruction of the ecological environment, even if it is the common problem (Sun et al, 2021;. Scholars found that China has achieved a win-win situation of environmental protection and economic growth during the industrial transformation and upgrading in recent years by including industrial wastewater and exhaust emissions in the assessment of ecological efficiency .…”
Section: Ecological Efficiency Estimationsmentioning
confidence: 99%
“…For 161 middle-income and high-income countries, technological innovation can bring 162 sustainable progress. However, for low-income countries, there is no causal relationship 163 between technological innovation and sustainable development (Ormi, 2020;Ormi, 164 2018;Surender and Shunsuke, 2010).…”
Section: Technological Innovation and Ecological Efficiencymentioning
confidence: 99%
“…Tourism has solidified its role as the strategic-pillar industry in China [1], accounting for 6.69% of the total gross domestic product (GDP) in 2019. For a long time, tourism has been regarded as an industry with low-carbon and environmental protections [2]. Therefore, adequate attention is not paid to the pollution brought by tourism industry in China.…”
Section: Introductionmentioning
confidence: 99%